Clinical and Clinicopathological Factors Associated with Survival in 44 Horses with Equine Neorickettsiosis (Potomac Horse Fever). (1st October 2013) - Bertin, F.R.; Reising, A.; Slovis, N.M.; Constable, P.D.; Taylor, S.D.
<x xml:space="preserve">Abstract</x> Background The epidemiology of equine neorickettsiosis (EN) has been extensively studied but limited clinical and clinicopathological data are available concerning naturally infected horses. Hypothesis Factors predictive of survival will be identified in horses diagnosed with EN. Animals Convenience sample of 44 horses with EN admitted to 2 referral institutions. Methods A retrospective study was performed. A diagnosis of EN was based on the presence of positive blood or fecal PCR. Results The most common clinical signs included diarrhea (66%), fever (50%), anorexia (45%), depression (39%), colic (39%), and lameness (18%). The median duration of hospitalization was 6 days and 73% of horses survived to discharge. Laminitis was present in 36% of horses, 88% of which were affected in all 4 feet. Serum creatinine and urea nitrogen concentrations, as well as RBC count, blood hemoglobin concentration, hematocrit, band neutrophils, serum AST activity, serum CK activity, and anion gap, were significantly (P < .05) higher in nonsurvivors. Serum chloride and sodium, concentrations as well as duration of hospitalization were significantly lower in nonsurvivors. The results of forward stepwise logistic regression indicated that blood hemoglobin concentration on admission and antimicrobial treatment with oxytetracycline were independent factors associated with survival. Conclusions and Clinical Importance Severity of colitis as reflected by electrolyte loss, hemoconcentration, and prerenal azotemia were predictors of survival in horses diagnosed with EN. Treatment with oxytetracycline was associated with increased survival.